An NMR‐Driven Crystallography Strategy to Overcome the Computability Limit of Powder Structure Determination: A Layered Aluminophosphate Case. Issue 16 (6th March 2013) - Bouchevreau, Boris; Martineau, Charlotte; Mellot‐Draznieks, Caroline; Tuel, Alain; Suchomel, Matthew R.; Trébosc, Julien; Lafon, Olivier; Amoureux, Jean‐Paul; Taulelle, Francis
<x xml:space="preserve">Abstract</x> Just in time: An NMR‐driven structure resolution that allows structure determination from the powder diffraction data of a highly complex layered aluminophosphate, and was otherwise not possible despite the high quality of the synchrotron diffraction data, is proposed. This study shows that the strategy is general and allows reduction of the number of free parameters to search for a structure and converge under the limit of the combinatorial explosion of computing time (see figure).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>